Joost van den Vondel (1587-1679) : Dutch playwright in the golden age - Bloemendal, Jan, 1961-; Korsten, Frans-Willem (Drama and theatre in early modern Europe, 2012)
"Both historically and theoretically this book deals the work and the life of Joost van den Vondel, the most famous and controversial Dutch playwright in the Dutch Republic. Over twenty-five of his tragedies are analyzed, offering an overview of different theoretical approaches. Historically, Vondel is situated in his own times and in the present."--Publisher's description